2019
DOI: 10.1039/c8ce01766b
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-polymer guest exchange in a carbamazepine inclusion complex: structure, kinetics and implication for guest selection

Abstract: Solvent–polymer guest exchange in a carbamazepine inclusion complex in a stirred solution was studied and a mechanism was proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…Note, that these results coincide with those obtained for carbamazepin-containing solids using the XPac method [103].One of the carbamazepin pseudo-isostructural groups is represented by metastable polymorph II and its solvates and hydrates situated inside the channels formed by the hydrophobic aromatic surfaces of this molecule, which were found to act as stabilizers of this solid [104]. These solvent molecules within the channels can even be replaced with hydrophobic polymer guest molecules [105]. Comparison of an orthorhombic polymorph of trimeric perfluoro-ortho-phenylen mercury with its' three monoclinic polymorphs gives up to six similarly packed molecules.…”
Section: Crystal Packing Similarity Toolsupporting
confidence: 81%
“…Note, that these results coincide with those obtained for carbamazepin-containing solids using the XPac method [103].One of the carbamazepin pseudo-isostructural groups is represented by metastable polymorph II and its solvates and hydrates situated inside the channels formed by the hydrophobic aromatic surfaces of this molecule, which were found to act as stabilizers of this solid [104]. These solvent molecules within the channels can even be replaced with hydrophobic polymer guest molecules [105]. Comparison of an orthorhombic polymorph of trimeric perfluoro-ortho-phenylen mercury with its' three monoclinic polymorphs gives up to six similarly packed molecules.…”
Section: Crystal Packing Similarity Toolsupporting
confidence: 81%
“…[29][30][31] In our previous study, we showed that the linear polymer, poly(tetrahydrofuran) (PTHF), could also occupy these channels as guest and form a crystalline inclusion complex. 22 The CBZ framework structures of form II and drug-polymer inclusion complex crystals are the same with each other, as evidenced by their X-ray diffraction patterns. Unlike the other drugs in our previous studies on drug-polymer inclusion complexes, the channel-type structure of CBZ form II is apparently stable even without guest occupation, thus providing the rare opportunity to directly study the guest effect.…”
Section: Conrmation Of the Cbz-peg Ic And Cbz-pcl Ic Structuresmentioning
confidence: 80%
“…1) were similar to each other and all consistent with that of the form II crystal in the literature. 27 As in other drug-polymer inclusion complex and channel-type solvate crystals, [12][13][14][15][16][17][18][19][20][21][22][23] the guest molecules were in the disordered state and did not contribute to diffraction peaks in diffractograms. The two inclusion complexes were crystallized in the presence of excess polymers, which were removed by rinsing the samples with suitable solvents (water for the PEG and CCl 4 for the PCL systems, respectively).…”
Section: Conrmation Of the Cbz-peg Ic And Cbz-pcl Ic Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The work is expected to deepen our understanding of the nucleation of multi-component co-crystals.Entropy 2019, 21, 1032 2 of 12 compound (IC) during its crystal growth process [17]. The PEO/urea ICs consist of guest PEO chains residing in the cavities formed by the host urea molecules [18][19][20][21][22][23][24][25][26]. By replacing a small amount of urea with N,N -dimethyl urea with the PEO concentration unchanged, we could change the rate of secondary nucleation and determine the critical size of the secondary nuclei of the PEO/urea IC β crystal.…”
mentioning
confidence: 99%